A Dewetted-Dealloyed Nanoporous Pt Co-Catalyst Formed on TiO2 Nanotube Arrays Leads to Strongly Enhanced Photocatalytic H-2 Production - Ji, Lei; Spanu, Davide; Denisov, Nikita; Recchia, Sandro; Schmuki, Patrik; Altomare, Marco (Chemistry - An Asian Journal, 2020)
Pt nanoparticles are typically decorated as co-catalyst on semiconductors to enhance the photocatalytic performance. Due to the low abundance and high cost of Pt, reaching a high activity with minimized co-catalyst loadings is a key challenge in the field. We explore a dewetting-dealloying strategy to fabricate on TiO2 nanotubes nanoporous Pt nanoparticles, aiming at improving the co-catalyst mass activity for H-2 generation. For this, we sputter first Pt-Ni bi-layers of controllable thickness (nm range) on highly ordered TiO2 nanotube arrays, and then induce dewetting-alloying of the Pt-Ni bi-layers by a suitable annealing step in a reducing atmosphere: the thermal treatment causes the Pt and Ni films to agglomerate and at the same time mix with each other, forming on the TiO2 nanotube surface metal islands of a mixed PtNi composition. In a subsequent step we perform chemical dealloying of Ni that is selectively etched out from the bimetallic dewetted islands, leaving behind nanoporous Pt decorations. Under optimized conditions, the nanoporous Pt-decorated TiO2 structures show a>6 times higher photocatalytic H-2 generation activity compared to structures modified with a comparable loading of dewetted, non-porous Pt. We ascribe this beneficial effect to the nanoporous nature of the dealloyed Pt co-catalyst, which provides an increased surface-to-volume ratio and thus a more efficient electron transfer and a higher density of active sites at the co-catalyst surface for H-2 evolution.
CRIS-Team WoS Importer:2020-01-17

Electrochemically Faceted Bamboo‐type TiO2 Nanotubes Provide Enhanced Open‐Circuit Hydrogen Evolution - Ji, Lei; Zhou, Xuemei; Schmuki, Patrik (ChemElectroChem, 2019)
In this paper we prepare facetted “black” TiO 2 nanotube arrays (NTAs) with a bamboo-type structure which exhibits an enhanced performance for open-circuit H 2 generation without the use of any noble metal co-catalyst. The TiO 2 nanotubes were formed by applying alternating positive and negative voltages. During the electrochemical formation, not only a bamboo structure is formed but the tubes are reduced in the cathodic cycle. After a rapid annealing treatment of these tubes in air at 500 °C for 10 s, the bamboo rings (knots) provide (001) facets preferentially located at the knot, while (101) planes prevail on the smooth part of tube between knots, as shown by TEM. The short annealing time keeps Ti 3+ /oxygen vacancies (V O ) as co-catalytically active centers still preserved in the TiO 2 NTAs. The results of intensity modulated photocurrent spectroscopy (IMPS) and open-circuit potential decay measurements (V OC ) indicate that these faceted and reduced TiO 2 nanotube arrays provide an efficient separation and reaction of photo-generated charge carriers, leading to an improved photocatalytic H 2 evolution performance.
CRIS-Team Scopus Importer:2019-05-02
Keywords: bamboo-type structures; cathodic reduction; hydrogen evolution; materials science; nanotubes

Sulfur and Ti3+ co-Doping of TiO2 Nanotubes Enhance Photocatalytic H2 Evolution Without the Use of Any co-catalyst - Ji, Lei; Zhou, Xuemei; Schmuki, Patrik (Chemistry - An Asian Journal, 2019)
TiO2 nanotubes were successfully co-doped with sulfur and Ti3+ states using a facile annealing treatment in H2/H2S gas mixture. The obtained nanotubes were investigated for their photocatalytic performance and characterized by SEM, XRD, XPS, EPR, IPCE, IMPS and Mott-Schottky measurements. The synthesized co-doped TiO2 nanotubes show an enhanced photocatalytic hydrogen production rate compared to tubes that were treated only in pure H2 or H2S atmosphere—this without the presence of any co-catalyst. It was found that sulfur in co-doped TiO2 exists in the form of S2− and a small quantity of S4+/S6+, which leads to a narrowing of the band gap. However, the enhanced absorption of light in the visible range is not the key reason for the improved photocatalytic performance. We ascribe the enhanced photocatalytic activity to a synergetic effect of S mid-gap states and disordered Ti3+ defects that facilitate photo generated electron transfer.
CRIS-Team Scopus Importer:2019-07-19
Keywords: hydrogen evolution; nanotubes; oxygen vacancy; sulfur doping; titanium